The investigation of selected distinctive vegetations as natural dyes sources / Razis Rahim - Rahim, Razis (2012)
The colouring of textile with natural dyes from vegetation sources is receiving increasing attention‘ This study was carried out to investigate potential vegetations. Gluta aptera, Bixa oreIIana and Michelin champaca were selected as natural dye sources. Natural dyes from these sources were extracted via boiling with water and solvent extraction method using methanol. Liquid extracts were then convened into paste form using rotary evaporator and the dried pastes were then encapsulated with beta-cyclodextrin to form powder. The powder form is an ideal form of dyes since it is easy to handle with longer shelf life. The natural dyes were then used to dye 100% satin silk, 100% plain weave cotton and 100% plain weave polyester fabrics simultaneously with and without mordant. The absorbance of the natural dyes were measured using UV-Vis spectrophotometer at wavelength range of 200 to 700 nm. All dyed fabrics were then compared in term of color shades and colorfastness to washing, perspiration, rubbing and light. The dyed fabrics show moderate to good results for washing, perspiration and rubbing but poor light fastness. This finding would give added values to the uniqueness of natural dyed products.